A web-based screening model for climate risk to water supply systems in the northeastern United States. (November 2015) - Whateley, Sarah; Walker, Jeffrey D.; Brown, Casey
Abstract: The aim of this study is to describe the development and application of a web-based decision support tool (ViRTUE) for performing climate risk evaluations of water supply systems. The tool is designed for small-scale water utilities in the northeastern United States that may lack the resources for detailed climate change risk investigations. Development of this tool demonstrates a relatively new approach to web application development using the Shiny framework for the R programming language to create an interactive environment for stakeholders and water managers to explore climate vulnerabilities. Using a decision-scaling framework, the tool allows the user to perform a climate stress test to evaluate the performance and vulnerability to water supply shortfalls of local reservoir systems over a wide range of potential climate change scenarios using a generic systems model. Probabilities of future climate conditions derived from climate projections then help inform utility operators of impending risk. Highlights: We develop a web-based decision support tool for climate risk assessment. The tool allows users to perform a climate stress test on a water supply system. We illustrate a relatively new approach to web application development in R. The tool makes climate risk investigations more accessible to small utilities.